A note on range-kernel uncomplementation - Kubrusly Carlos; Duggal Bhagwati Prashad (Demonstratio Mathematica, 2017)
This note exhibits a Banach-space operator such that neither the range nor the kernel is complemented both for the operator and its adjoint